10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Background The genus Bordetella comprises 16 species of aerobic Gram-negative bacteria, with the most notable being B. pertussis, B. parapertussis and B. bronchiseptica. The latter stands out for its ability to infect various hosts, causing both respiratory and reproductive issues, such as endometritis and infertility in mares. These infections impair reproductive efficiency and facilitate the spread of the pathogen among susceptible animals. Objectives The present study aimed to report the isolation and molecular diagnosis of B. bronchiseptica associated with endometritis and infertility in mares in Brazil, as well as to evaluate the antimicrobial susceptibility profile of the isolates. Methods For this purpose, uterine lavage was collected from three Mangalarga Marchador mares using an aseptic technique with a transcervical probe and Ringer's lactate solution. The samples were centrifuged, cultured on MacConkey agar, blood agar and Sabouraud agar, and identified by biochemical characteristics. PCR was performed to amplify the flanking region of the flaA gene of B. bronchiseptica, followed by sequencing and analysis. Results The antibiogram was conducted using the agar diffusion method on Mueller-Hinton agar. Microbial culture identified B. bronchiseptica, confirmed by biochemical and molecular tests. The isolates showed resistance to multiple antibiotics, such as penicillins and cephalosporins. Main limitations No investigation into transmission routes, prevalence or risk factors in the broader equine population. Conclusion This study describes, for the first time in Brazil, the detection of B. bronchiseptica causing uterine infection and infertility in mares, expanding knowledge about its pathogenic potential. The results highlight the need to consider this bacterium in the diagnosis of reproductive disorders, even in the absence of respiratory manifestations.